In vivo molecular imaging of the neuroinflammatory response to peripheral acute bacterial infection in older patients with cognitive dysfunction: A cross-sectional controlled study - Silva, Ana Rita; Regueira, Patricia; Peres, André; Cardoso, Ana Luísa; Baldeiras, Inês; Santana, Isabel; Cerejeira, Joaquim (Frontiers in Aging Neuroscience, 2022)
Introduction: chronic neuroinflammatory events have been implicated in the pathophysiology of neurodegenerative conditions but no studies have directly examined the neuroinflammatory response to acute systemic infection in older people with dementia. The objective of this study was to determine the magnitude of the neuroinflammatory response triggered by acute systemic inflammation in older subjects with dementia and/or delirium compared to cognitively healthy controls. Methods: we recruited 19 participants (4 with delirium, 4 with dementia, 4 with delirium superimposed on dementia, 7 cognitively healthy) hospitalised with acute systemic bacterial infection not involving the Central Nervous System. Participants underwent [11C]-PK11195 PET and a neuropsychological assessment during hospital stay. The distribution volume ratio was estimated in the regions-of-interest using the Hammers' brain atlas. Results: In the subcortical analysis, we found that the cognitively healthy group presented regions with significantly higher DVR intensity than the other groups in the choroid plexus. Mean choroid plexus DVR positively correlated with the MoCA global score (r=0.660, p=0.037). Conclusion: this study suggests that dementia and/or delirium is associated with a reduced neuroinflammatory response to acute systemic bacterial infection which can be the result of an immunosuppressive brain environment.